Information disclosure, CEO overconfidence, and share buyback completion rates - Andriosopoulos, Dimitris; Andriosopoulos, Kostas; Hoque, Hafiz (Journal of Banking & Finance, 2013)
An open market share buyback is not a firm commitment, and there is limited evidence on whether firms repurchase the intended shares. Unlike US studies, we use data from unique UK regulatory and disclosure environment that allows to accurately measure the share buyback completion rates. We show that information disclosure and CEO overconfidence are significant determinants of the share buyback completion rate. In addition, we find that large and widely held firms that conduct subsequent buyback programs and have a past buyback completion reputation exhibit higher completion rates. Finally, we assess whether other CEO characteristics affect buyback completion rates and find that firms with senior CEOs who hold external directorships and have a longer tenure as CEO are more likely to complete the buyback programs. In sum, our results suggest there is a clear relationship between information disclosure, CEO overconfidence, and buyback completion rates.